African Futures - Greiner, Clemens; Van Wolputte, Steven; Bollig, Michael (Africa-Europe Group for Interdisciplinary Studies, 2022)
This collection brings together scholars from different disciplines. In short and provocative essays, they shine their light on the often ambivalent and contradictory possibilities and challenges people in Africa are facing. Africa, indeed, has many futures.